PERANCANGAN APLIKASI PENGENALAN LITERASI COVID-19 MENGGUNAKAN ACTIONSCRIPT 3.0 PADA MACROMEDIA FLASH - Jeffry Andhika Putra; Erry Maricha Oki Nur Haryanto (Informasi Interaktif, 2022)
The Covid-19 pandemic that has hit the world is a phenomenon that has never been predicted before in modern civilization. The increasingly widespread Covid-19 pandemic requires everyone to disciplinedly apply health protocols (use masks, maintain physical distance, wash hands with soap, and stay away from crowds). In addition to maintaining cleanliness, social distancing is the most effective step to avoid contracting Covid-19. A public policy will be effective If the public supports it, Large-Scale Social Restrictions (PSBB) are one of the efforts that the Government can take to deal with the spread of the Covid-19 pandemic.The current era of information flows quickly spreads to all corners of the world. information through the media in different forms in the form of images, sound, as well as video, as well as in applications. These computer applications are generally in the form of term data processing programs, work sheet data, and media data. Personal computer software is designed to make it easier for users to do things using a personal computer. The global pandemic requires many parties, including educational institutions, to make discoveries on learning media. This study designed a learning application for knowledge literacy about Covid-19, so that it can convey knowledge literacy for the protection and prevention of the spread of the Covid-19 virus. The system will be designed using the Macromedia Flash framework or SDK (Application Development Kit) using the ActionScript 3.0 method so that it can run on computer platforms and operating systems.Keywords: Learning Application, Actionscript 3.0, Multi-Platform Application, Literacy, Covid-19.